Cognitive representation of gender typicality and its effects on linguistic processing - Reali, Chiara (2016)
The present research includes a series of studies which investigate the effects of cognitive representation of gender roles on reading comprehension processes. The work tests a description-based anaphor resolution paradigm which replaces classical role noun antecedents through role descriptions not containing any grammatical gender cue to the referent gender. This solution allows a cross-linguistic comparison between a grammatical gender language (German) and a natural gender language (English). Moreover, the research analyzes the impact of gender representations on thematic role assignment during sentence reading. The research employs the eye-tracking methodology to document the time-course of gender typicality/stereotype activation and its effect on anaphor resolution processes.